The democratic output legitimacy of international organizations - Jens Steffek (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
In this article I discuss output legitimacy as a category of normative analysis of international organizations (IOs). I first take issue with the widespread view that output legitimacy is just a synonym for organizational effectiveness or efficiency, and unrelated to democracy. Against this view, I argue that output legitimacy has an important democratic dimension. The touchstone of 'democratic output legitimacy' is the extent to which systems of governance generate results that cater to the public interest. This notion of democratic output legitimacy is then applied to IOs. The ability of IOs to safeguard a transnational public interest hinges on i) their ability to keep powerful (state and non-state) actors in check; ii) the epistemic quality of their decision-making procedures; iii) their respect for human and civil rights. Attaining these qualities may require shielding IOs from the input dimension of the international political process. I warn that some strategies to improve the democratic input legitimacy of IOs may enhance the power of strong nations over weaker ones, and of well-organized industry lobbies over other interests. – – Der vorliegende Beitrag diskutiert Output-Legitimität als Kategorie normativer Analyse internationaler Organisationen (IOs). Dabei geht er zunächst auf eine weit verbreitete Ansicht ein, der zufolge Output-Legitimität lediglich ein Synonym für organisationale Effektivität oder Effizienz ist, ohne dabei einen Bezug zur Demokratie herzustellen. Im Gegensatz dazu wird hier die Auffassung vertreten, dass Output-Legitimität über eine bedeutende demokratische Dimension verfügt. Als Prüfstein demokratischer Output-Legitimität wird angelegt, inwiefern Governance-Systeme Ergebnisse generieren, die sich am öffentlichen Interesse orientieren. Anschließend wird dieses Verständnis demokratischer Output-Legitimität auf IOs angewendet. Die Fähigkeit von IOs, ein transnationales öffentliches Interesse abzusichern ist abhängig von i) ihrer Fähigkeit, einflussreiche (staatliche und nicht-staatliche) Akteure unter Kontrolle zu halten; ii) der epistemischen Qualität ihrer Entscheidungsverfahren; iii) der Achtung der Menschen- und Bürgerrechte durch die IO. Um dies zu erreichen, kann es erforderlich sein, IOs von der Input-Dimension des internationalen politischen Prozesses abzuschirmen. Der Beitrag warnt damit zugleich davor, dass einige Strategien zur Verbesserung der demokratischen Input-Legitimität von IOs die Macht stärkerer über schwächere Staaten oder gut organisierter Industrielobbys über andere Interessen vergrößern könnten.
Keywords: 320; international organizations; legitimacy; democratic legitimacy; output legitimacy; internationale Organisationen; Legitimität; demokratische Legitimität; Output-Legitimität